2013
DOI: 10.1111/maps.12109
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic and chemical variation of organic nanoglobules in primitive meteorites

Abstract: Abstract-Organic nanoglobules are microscopic spherical carbon-rich objects present in chondritic meteorites and other astromaterials. We performed a survey of the morphology, organic functional chemistry, and isotopic composition of 184 nanoglobules in insoluble organic matter (IOM) residues from seven primitive carbonaceous chondrites. Hollow and solid nanoglobules occur in each IOM residue, as well as globules with unusual shapes and structures. Most nanoglobules have an organic functional chemistry similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
117
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(139 citation statements)
references
References 90 publications
(152 reference statements)
22
117
0
Order By: Relevance
“…9). These observations are in agreement with previous nanoSIMS analyses of Bells De Gregorio et al, 2013) …”
Section: N and C Isotope Compositionssupporting
confidence: 83%
“…9). These observations are in agreement with previous nanoSIMS analyses of Bells De Gregorio et al, 2013) …”
Section: N and C Isotope Compositionssupporting
confidence: 83%
“…In addition, recent studies showed variety of globule morphologies in CR, CM (Changela et al, 2012(Changela et al, , 2013De Gregorio et al, 2013) and CI, CO carbonaceous chondrites , and suggested modification of the morphology of organic nanoglobule during aqueous alteration on the parent body. Therefore, the morphology of organic matter (aggregated globules and/or particles and non-aggregated globules) in Murchison and NWA 801 might record the effect of aqueous alteration.…”
Section: Morphology Of the Isotopically Anomalous Organic Mattermentioning
confidence: 99%
“…
The presence of nano-scale, roughly spherical carbonaceous features has been shown in several samples of chondritic meteorites [1][2][3][4]. There have been a few proposed mechanisms by which these carbon nanoglobules may form [2,5].
…”
mentioning
confidence: 99%